Recent Advances in Conjugated Graft Copolymers: Approaches and Applications - Jarosz, Tomasz (Molecules, 2019)
The main goal of this mini review is to summarise the most recent progress in the field of conjugated graft copolymers featuring conjugation across the main chain, across side chains or across both. The main approaches to the synthesis of conjugated graft copolymers are highlighted, and the various trends in the development of new copolymer materials and the intended directions of their applications are explored.